Pengaruh Kepuasan Nasabah Terhadap Menggunakan Mobile Banking (M-Banking) Pada Bank BCA Cabang Banda Aceh - Syamsul Rizal; Munawir Munawir (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2017)
The purpose of this study is to determine the effect of service quality to consumer decisions using M-Banking at Bank BCA Branch Banda Aceh. This research was conducted at Bank BCA Branch of Banda Aceh to M-Banking consumer, and the object of research is about consumer's satisfaction in using M-Banking. Sampling was done by